2002
DOI: 10.1046/j.1365-2958.2002.03050.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics that inhibit cell wall biosynthesis induce expression of the Bacillus subtilisσW and σM regulons

Abstract: SummaryBacillus subtilis encodes seven extracytoplasmic function (ECF) sigma factors. The s W regulon includes functions involved in detoxification and protection against antimicrobials, whereas s M is essential for growth at high salt concentrations. We now report that antibiotics that inhibit cell wall biosynthesis induce both s W and s M regulons as monitored using DNA microarrays. Induction of selected s W -dependent genes was confirmed using lacZ reporter fusions and Northern blot analysis. The ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
261
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(282 citation statements)
references
References 51 publications
21
261
0
Order By: Relevance
“…When similar experiments were performed in B. subtilis, 10 min exposure was enough to obtain the induction of 129 genes (Cao et al, 2002), suggesting that some time is required for vancomycin to cross the mycobacterial outer membrane and exert its action. Quantitative RT-PCR was used to validate the differential expression of selected genes (Supplementary Tables S2 and S3, available with the online version of this paper).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…When similar experiments were performed in B. subtilis, 10 min exposure was enough to obtain the induction of 129 genes (Cao et al, 2002), suggesting that some time is required for vancomycin to cross the mycobacterial outer membrane and exert its action. Quantitative RT-PCR was used to validate the differential expression of selected genes (Supplementary Tables S2 and S3, available with the online version of this paper).…”
Section: Resultsmentioning
confidence: 93%
“…1a). A 10X-MIC of vancomycin was also used by Cao et al (2002) in B. subtilis to identify an inducible defensive response against antibiotics coordinated by alternative sigma factors. Subinhibitory conditions were determined by growing bacteria in the presence of decreasing vancomycin concentrations (twofold serial dilutions) starting from the MIC (40 mg ml 21 ) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell membrane is the first barrier to an increased ionic strength, and the sensing mechanism would take place in it (Poolman et al, 2002(Poolman et al, , 2004. In addition, several sigma factors required for extracytoplasmic functions (membrane and wall synthesis) have been shown to respond to stress effectors (Cao et al, 2002). In particular, Horsburgh & Moir (1999) showed that in B. subtilis, the sigM gene product is required for normal cell growth under salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…ECF s factors regulate the expression of target genes in response to changing physicochemical conditions in the cellular environment (Helmann, 2002). In the case of SigO and RsoA, the two-subunit s factor is expressed in the cell after exposure to certain cell-wall-acting antibiotics and acid stress conditions (Cao et al, 2002;Hachmann et al, 2009;MacLellan et al, 2009b). The SigO-RsoA regulon member gene rsiO (formerly known as yvrL) (see Fig.…”
Section: Introductionmentioning
confidence: 99%